Geomorphologic Map of the Brazilian Cerrado by geomorphometric archetypes - Rocha, Ana Beatriz de Alcantara; Barbosa, Vitória Rodrigues Ferreira; Faria, Karla Maria Silva; Martins, Eder de Souza; Soares Neto, Gervásio Barbosa (Revista Brasileira de Geomorfologia, 2022)
The Brazilian Cerrado is the second largest biome in Brazil, occupying approximately 25% of the national territory. It is characterized by an expressive biodiversity of fauna and flora, and it is considered the richest savanna in the world. Despite its environmental importance, it is considerably endangered and still undervalued in terms of conservation. Due to its flat lands, agricultural activities are largely developed in the Cerrado. Thus, more detailed studies in this region are necessary to help define mitigation measures against degradation, as well as conservation plans. This paper sets out to represent the geomorphology of the Cerrado based on geomorphometric parameters, using a semi-automatic relief classification method. Four metric parameters were considered for defining and characterizing the relief units: available relief, slope, orientation and shapes of the slopes. Representing geomorphological models with these parameters enables more reliable descriptions of real conditions. The geomorphological mapping of the Cerrado via mathematical modelling allows describing its key geomorphometric archetypes through six metric relief-classes that represent their actual conditions.